Analisis Pentingnya Perhitungan Harga Pokok Produksi dan Harga Pokok Penjualan untuk Optimalisasi Harga Jual Produk UMKM - Liza Novietta; Ruswan Nurmadi; Kersna Minan (Jurnal Akuntansi, Manajemen dan Ekonomi Digital, 2022)
MSME actors often only focus on how to make their business profitable and survive, not on how to optimize profits and business can develop. One way to obtain optimum profit is to set the optimum selling price as well, by calculating and determining the cost of production and cost of goods sold. Forum Akademisi dan Praktisi Desa (FAPDes), in which Universitas Harapan Medan is one of the higher education institutions that joins it, sees this as a necessity for MSME actors. Hopefully, that in the future MSME actors can compile simple financial reports, including the cost of production and the cost of goods sold, so that the selling price of the product can be optimal and the profit obtained is maximized.Keywords: MSMEs, Financial Report, Cost of Production, Cost of Goods Sold, Selling Price, Profit